Diseconomies Of Scale And Development - Olson, Mancur (1995)
The supply of collective goods requires a state that is capable of managing large-scale organizations, a feature that is particularly scarce in underdeveloped countries. We should not, then, be surprised In¡ the fact that government regulations and public services work less well in developing than in developed countries. Whatever the optimal role of government may be in developed countries, it will be smaller in developing countries until they learn to deal with large-scale organizations in an efficient way.